Biocompatible gelatin-coated ferrite nanoparticles: A magnetic approach to advanced drug delivery - Varda Shakeel; Iftikhar Hussain Gul; Peter John; Attya Bhatti (Elsevier, 2024)
Nanotechnology has transformed drug delivery, offering opportunities to enhance treatment outcomes while minimizing adverse effects. This study focuses on gelatin-coated cobalt and manganese ferrite nanoparticles for potential drug delivery applications. The synthesis involved a co-precipitation method, and the nanoparticles were characterized using various techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, and vibrating sample magnetometer (VSM). Results revealed stable structures, distinct chemical features introduced by gelatin coating, and unique magnetic properties. The hemolysis assay demonstrated reduced hemolytic activity with gelatin coating, enhancing biocompatibility. Drug release studies indicated differential release profiles, with gelatin-coated cobalt ferrite exhibiting higher drug release compared to gelatin-coated manganese ferrite. The Higuchi model supported diffusion-controlled drug release for gelatin-coated cobalt ferrite. These findings suggest the potential of gelatin-coated ferrite nanoparticles for controlled and targeted drug delivery, highlighting their significance in advancing nanomedicine.